Stability Control for Dynamic Walking of Bipedal Robot with Real-time Capture Point Trajectory Optimization - Kim, In Seok; Han, Young Joong; Hong, Young Dae (Journal of Intelligent and Robotic Systems: Theory and Applications, 2019)
This paper proposes a stabilization method for dynamic walking of a bipedal robot with real-time optimization of capture point trajectories. We used the capture point trajectories to generate the control input, which is the desired zero moment point (ZMP) with a sliding-mode ZMP controller to follow the desired ZMP. This method enables the robot to implement various dynamic walking commands, such as forward stride, lateral stride, walking direction, single support time, and double support time. We also adopted enhanced dynamics with the three mass linear inverted pendulum model (3M-LIPM). First, the compensated ZMP is calculated by both walking commands and kinematic configuration of the robot in closed form. Then, the walking pattern is obtained by using initial and boundary conditions of the 3M-LIPM, which satisfies the walking commands. The capture point (CP) trajectory is optimized in real time to control the walking stability and a capture point tracking controller is used for tracking the optimized CP trajectory, which generates an optimal control input that is near the center of the support polygon. The performance of the proposed stabilization method was verified by a dynamics simulator, Webots, and comparison with the original capture point controller-based walking algorithm is presented.
Keywords: Capture point dynamics-based walking; Divergent component of motion; Inverted pendulum model; Real time; Walking pattern generation; Capture point dynamics-based walking; Divergent component of motion; Real-time walking optimization; Three mass inverted pendulum model; Walking pattern generation